Parents’ refusal to vitamin-K supplementation among neonates and its association with vaccine refusal: A systematic review and meta-analysis - Tahir Mehmood Khan; Naeem Mubarak; Amal Suleimen; Ammar Ali Saleh Jaber; Mirza Rafi Baig (Journal of the Pakistan Medical Association, 2022)
Objective: This systematic review and meta-analysis aims to estimate the prevalence of neonatal vitamin K prophylaxis refusal among parents and its possible association with subsequent vaccine hesitancy or refusal. Method: The databases searched included PubMed, Cochrane Library, Embase via Ovid, CINAHL Plus and Medline via EBSCOhost, ProQuest and PsycINFO from inception to 31 Aug 2017. Keywords, such as “vitamin K”, “refusal”, “decline”, “hesitancy”, and “vaccination” were used to identify potential studies. Analysis of proportions was conducted, while odd ratios and relative risks were estimated using the random effect model. Results: Of the 2216 studies identified, 8(0.36%) were subjected to qualitative analysis; 4(50%) retrospective cohort studies and 4(50%) cross-sectional studies. Overall, 6(75%) studies were of good quality, while 2(25%) were ranked as of fair quality. Of the 273,714 parents, 3,136(1.14%) refused to opt for the vitamin K prophylaxis. Meta-analysis concluded that refusal to vitamin K prophylaxis was significant among the included studies ((p<0.184). Conclusion: The overall risk of refusal to essential vaccination among vitamin K prophylaxis refusal group was 6.45 times compared to the group that accepted vitamin K prophylaxis. Key Words: Vaccine hesitancy, Vitamin K prophylaxis, Vaccine refusal, Newborn, Parents.